ANALISIS KEPUASAN PENGGUNA APLIKASI TRANSPORTASI ONLINE MENGGUNAKAN EUCS - Gustin Setyaningsih (Hemispheres Press, 2023)
One of the most important factors influencing the success of an application is user satisfaction. There have been many online transportation applications offered to the public, making the competition between these online transportation companies even stronger in the market. One of the online transportation applications is Gojek. This online transportation application is easy to use and most in demand by the public. The purpose of this study is to find out how satisfied end users are with Gojek and what factors contribute to user satisfaction. The End User Computing Satisfaction (EUCS) method was used in this study. One dependent variable is satisfaction, and the EUCS method has five independent variables: content, accuracy, format, ease of use and timelines. The population of this study was the people of Banyumas Regency, using the sampling formula, 100 people were selected as the research sample from this population. From the results of data analysis, it was found that five independent variables were content, accuracy, format, ease of use and timelines which had been tested for their significant effect on satisfaction. It was found that there was a significant effect on the variables content, accuracy, format, ease of use on the satisfaction variable. While the timeliness variable has no significant effect on satisfaction, so it can be said that hypotheses 1, 2, 3, 4 are accepted, while hypothesis 5 is rejected. Then obtained a percentage of 77%, there is a close relationship between these independent variables and the dependent variable, and 59.3% of the satisfaction variable can be explained by the independent variable. While the remaining 40.7% is influenced by other variables outside of the model being studied.